Association of circulating branched-chain amino acids with risk of moyamoya disease - Zeng, Chaofan; Ge, Peicong; Liu, Chenglong; Yu, Xiaofan; Zhai, Yuanren; Liu, Wei; He, Qiheng; Li, Junsheng; Liu, Xingju; Wang, Jia; Ye, Xun; Zhang, Qian; et al. (Frontiers in Nutrition, 2022)
Objective Branched-Chain Amino Acids (BCAAs) has been identified as a risk factor for circulatory disease. Nevertheless, the effects and mechanisms of BCAAs on the risk of moyamoya disease (MMD) remain unrecognized. Hence, we aimed to elucidate the association between circulating BCAAs and the risk of MMD and clinical subtypes. Methods We conducted a case-control study of 360 adult MMD patients and 89 matched healthy controls consecutively recruited between September 2020 and December 2021. Serum level of BCAAs was quantified by liquid chromatography-mass spectrometry. The associations between BCAAs and risk of MMD were evaluated. Results Increased level of serum BCAAs was observed in MMD patients (P < 0.001). After adjusting for traditional confounders, the elevated BCAAs level was significantly associated with the risk of MMD (Q4 vs. Q1: odds ratio, 3.10 [95% CI, 1.29–7.50]). The risk of subtypes in MMD also increased with each increment in the quartiles of BCAAs. Furthermore, BCAAs offered substantial improvement in risk reclassification and discrimination for MMD and subtypes. Conclusion Higher level of circulating BCAAs was associated with increased risk of MMD and clinical subtypes. This study will help to elucidate the pathogenesis of MMD, which may provide the support for facilitating the treatments and preventions.